Effect of supplementing specific nutrients under calorie restriction on exercise performance in mice - YUAN Jiaqi; WANG Peng; LI Weifang (陆军军医大学学报)
Objective‍　‍To develop a composite nutritional preparation that can effectively improve exercise performance under calorie restriction (CR) condition. Methods‍　‍A total of 24 male C57BL/6J mice (weighing 23~26 g, 8 weeks old) were randomly divided into control group (CON), CR, CR+basal nutrient group (CRN1), and CR+compound nutrient group (CRN2). All groups underwent moderate-intensity running training 5 d per week, for totally 3 weeks. The grip strength of the forelimbs were measured weekly, and in 3 weeks after training, exhaustion and post-exhaustion distance tests were conducted to evaluate exercise performance. Blood biochemical indicators, levels of skeletal muscle and liver redox biomarkers, and histopathological conditions were measured and observed. Results‍　‍After 21 d of intervention, the CR group and CRN1 group had the post-exhaustion running distance prolonged by 278% and 289%, respectively, reduced blood glucose level, and decreased muscle mass, subcutaneous fat and epididymal fat mass when compared with the CON group (P<0.05). Compared with the CON group, the CRN1 and CRN2 groups demonstrated significantly higher gastrocnemius glycogen content. The CRN2 group obtained even longer post-exhaustion distance (increased by 52% and 36% respectively, compared with the CON group and CRN1 group, P<0.05), enhanced grip strength of the forelimbs (raised by 9%, 17% and 15%, respectively than the CON, CR and CRN1 groups, P<0.05), elevated brown fat mass (compared to the CON group and CRN1 group, P<0.05), increased blood glucose level (compared to the CRN1 group, P<0.05), decreased blood low-density lipoprotein cholesterol level (compared to the CON and CR groups, P<0.05), and increased glutathione peroxidase content in the gastrocnemius muscle (compared to the CON group, P<0.05). Conclusion‍　‍Supplementing with compound nutritional supplements in mice under CR can promote exercise performance, including improving fatigue recovery after exhaustive exercise and enhancing forelimb grip strength.